Postharvest treatments to reduce chilling injury in summer squash (Cucurbita pepo) fruits during storage - KANNAUJIA, PANKAJ KUMAR; ASREY, RAM; SINGH, AWANI KUMAR; VARGHESE, ELDHO (The Indian Journal of Agricultural Sciences, 2019)
The present study was carried out to minimize postharvest problems of chilling injury during cold storage by the application of anti-chilling compounds, viz. salicylic acid (SA), sodium nitroprusside (SNP) and a nitric oxide donor (NO). For minimizing chilling injury symptoms summer squash (Cucurbita pepo L.) fruits were treated with salicylic acid (1.0–1.5 mM) and sodium nitroprusside(1.0–1.25 mM) followed by cold storage at 5±2ºCand 85–90% relative humidity. Among the used anti-chilling molecules, salicylic acid @1.0 mM provides the best results for minimizing chilling injury score (0.74) and proline content (333.87 μg/g) during cold storage. Fruits treated with 1.5 mM SA and 1.0 mM SNP showed a 37.42% and 27.42% lower electrolyte leakage as compared to control. In the case of malondialdehyde (MDA) content, 1.0 and 1.5 mM SA dose showed a ≈39% and ≈36% lower content than control. Higher fruit firmness (7.07 N) retention was found in 1.0 mM sodium nitroprusside and followed by 1.0 mM salicylic acid (6.96 N) treated fruits. Overall 1.0 mM salicylic acid followed by 1.0 mM sodium nitroprusside proves better for prevention of chilling injury and lower production of malondialdehyde content.